The production and mapping of wheat-rye introgression lines exploiting Ph1 - Heath, Jack W. (2019)
Wheat is a staple food source across the globe. To cope with the increasing problems of global food security, higher yielding, stress tolerant wheat cultivars are necessary. This thesis describes a method of introgressing rye chromatin into wheat to make beneficial rye traits available in wheat germplasm and thus to facilitate the use of rye traits in the breeding of elite wheat cultivars.